Antioxidant and Anti α-amylase activities of Polar Extracts of Mitracarpus hirtus and Saba Senegalensis and the combination of their Butanolic Extracts - Sarr, Fatou Bintou; Sy, Gata Yoro; Cabral, Matild (International Research Journal of Pure and Applied Chemistry, 2023)
Diabetes mellitus is a major public health disease, and it affects all segments of the population around the world. The progression of this disease is worrying, 460 million in 2019, the number of diabetics is estimated in 2045 at 700 million worldwide. The antioxidant and antidiabetic activities of the ethyl acetate (EA) and Butan-1-ol (But-ol) fractions of M hirtus and Saba senegalensis are studied in this work. The results revealed that the fractions possessed flavonoid, tannins, terpenes and sterols; and exhibit potent radical scavenging activity using DPPH as substrate. The butanolic fractions exhibited more significantly α-amylase inhibitory activities than the ethyl acetate fractions. The IC50 values of butanolic fractions are 0.099 and 0.41 mg/ml respectively for M hirtus and S Senegalensis versus 0.44 and 1.45mg/ml ethyl acetate fractions. The combined butanol fractions of the two plants do not lead to the expected synergetic activities. Thus, it could be concluded that due to the presence of antioxidant components in the plant, extracts have well prospective for the management of diabetes and the related condition of oxidative stress.
International Research Journal of Pure & Applied Chemistry 22(9): 1-8, 2021; Article no.IRJPAC.77260 ISSN: 2231-3443, NLM ID: 101647669
Keywords: Dioum, Mbaye Diaw; Sene, Madieye; Ndong, Awa; Sall, Cheikh; Faye, Ousmane; Université Cheikh Anta Diop; Sénégal; CEA-AGIR; Diabetes; Mitracarpus hirtus; Saba senegalensis; antioxydant; antidiabetes